Properties and dynamics of two-dimensional colloid-polymer mixtures - Mordan, M (2020)
The depletion interaction, aggregation behaviour and network formation in quasi-two-dimensional colloid-polymer solutions are studied using optical microscopy and optical tweezing. First, the polymer used as a depletant throughout this thesis, xanthan gum, is characterised. The intrinsic viscosity, coil overlap concentration and radius of gyration are determined using a novel combination of passive micro-rheology and polyelectrolyte rheology theory. The Mark-Houwink coefficient is also found, which can be used to characterise the molecular weight of future xanthan samples, under the experimental condition described herein. Next, the depletion interaction between two superparamagnetic particles, near to a wall, is measured using a combination of optical tweezer microscopy, statistical analysis and first passage time theory. The interaction strength is measured for two concentrations of polymer in the dilute regime and one in the semi-dilute regime. Due to the particles' superparamagnetic nature, their response to an applied magnetic field is used to probe the semi-dilute regime which would not be possible by passive methods alone. Having characterised the interparticle attraction range and strength, the two-dimensional aggregation behaviour of the same colloid-polymer system is investigated, at three successively increasing concentrations and analysed using established aggregation theory. Past a polymer concentration threshold, the strength of interaction is found to have no measurable effect on the systems aggregation kinetics. Finally, the network formation as a function of polymer concentration is analysed. The network strand thickness and coordination number distributions are found to have a strong dependence on the interparticle interaction strength. The structural dynamics and network coarsening behaviour pre and post network formation is also shown to depend strongly on the polymer concentration. Cluster and network dynamics are quantified using bond-order orientational analysis which shows a competition between inter-cluster particle rearrangements and cluster aggregation at low polymer concentrations that are significantly diminished at higher polymer concentrations.